Formation of chemical short range order and its influences on the dynamic/mechanical heterogeneity in amorphous Zr–Cu–Ag alloys: A molecular dynamics study - Tang, Chao (2018)
The chemical short range order of metallic glasses is expected to be correlated with their mechanical properties. In this article, classic molecular dynamics simulations of amorphous Zr45Cu45Ag10 alloys were carried out to reveal such links in metallic glasses. Our calculations of Warren–Cowley parameter indicate the growth of chemical short range order during supercooling process, which also depends on the effective cooling rates. The chemical short range ordering is related to the energetic stability of the system. Based on the chemical preference or avoidance for different bonds, the model is separated into Cu-rich regions and Ag-rich regions. Simulated structural relaxation and shear loading process were performed to study how chemical bonds affect the distribution of dynamic and mechanical heterogeneity in our systems. The Cu-rich regions exhibit slower dynamics and higher shear resistance, whereas Ag-rich regions have faster dynamics and prefer to be plastically deformed.